Synthesis of Sulfoximines through Selective Sulfur Alkylation of Sulfinamides Generated In Situ from β-Sulfoximine Esters - Han, Min; Luo, Lanxin; Tang, Zhuo; Li, Guang-xun; Wang, Qiwei (Synlett, 2023)
Over the past decade, the incidence of sulfoximine functional groups in pharmaceuticals and agrochemicals has increased significantly. This increase has led to a range of useful strategies for installing a S(VI) functionality into complex organic molecules. Conventional synthetic methods for forming α-substituted sulfonimidoyl motifs rely on late-stage modifications at sulfur and involve multistep routes. We report the development of an efficient and general method for the synthesis of various α-arylated sulfoximines through a selective S-alkylation. This strategy uses economical and readily available β-sulfoximine esters as precursors of sulfinamides and has been demonstrated by the preparation of 31 sulfoximines in good yields (up to 87%).
Keywords: sulfoximines; S-alkylation; sulfinamides; sulfoximine esters